国際幹細胞学会（ISSCR）「幹細胞研究・臨床応用」ガイドラインの解説 - 井上, 悠輔 (Organ Biology, 2017)
Main points of ISSCR (The International Society for Stem Cell Research)’s amended guidelines of 2016 were summarized. The guidelines are presented as a single document based on the preceding two ISSCR guidelines, with a preamble that articulates core ethical principles for guiding both basic and clinical stem cell research: the integrity of the research enterprise, the primacy of patient welfare, respect for research subjects, transparency, and social justice. As they concern irreproducible results and the incomplete reporting of findings from preclinical studies, they strongly require rigorous demonstration of preclinical evidence and rigorous peer review of clinical trial protocols and study reporting.